The Oral Anticoagulants Administration in Elderly Patients with Geriatric Syndromes: What's New? - N. M. Vorobyeva; O. N. Tkacheva (Столичная издательская компания, 2020)
The administration of oral anticoagulants in elderly patients with geriatric syndromes such as senile asthenia syndrome, falls and high risk of falls, dementia, polymorbidity, polypharmacy are discussed in the article. The evidence base for the anticoagulants taking in patients with atrial fibrillation aged ≥75, ≥80, ≥85 and ≥90 years, in patients with atrial fibrillation and various geriatric syndromes, as well as in elderly patients with venous thromboembolic complications and frailty syndrome is presented. Most studies indicate significant advantages of direct oral anticoagulants (dabigatran, rivaroxaban, apixaban, and edoxaban) over the vitamin K antagonist warfarin in elderly patients with geriatric syndromes. An updated version of the FORTA consensus document, which aims to optimize the prescription of medicines for the elderly, is also presented. Apixaban has a FORTA-A safety class and is the safest oral anticoagulant in elderly patients.